Crime Of Theft With Violence Against Minors as Perpetrators - Siregar, Nyesti; July Esther; Lesson Sihotang (Indonesian Journal of Law and Justice, 2025)
The research diacusses the Crime of Theft of Minors as Perpetrators with an example of decision no.36/Pid.Sus.Anak/2024/PN.Mdn. The case study approach is normative juridical law, studying, analyzing, by observing and understanding cases related to issues and legislative approaches related to legal issues in terms of legal principles, doctrines and jurisprudence. Author Data Creation Primary, Secondary, and Tertiary Data Sources focus on literature research using qualitative analysis by observing data obtained by interconnecting with several literature in the form of scientific works, books, the internet, and legal journals related to problem analysis with conclusions in knowing the Application of Law and the Basis of Judges' Considerations in providing punishment as accountability for actions committed by children,  Children, in addition to having factors that encourage the occurrence of a criminal act, have a different position from adults in the justice system and need guidance and rehabilitation to prevent criminal behavior in the future and the basis for the judge's consideration provides a deterrent effect so that it does not happen again in the future against the Crime of Theft with Violence against Minors as the perpetrator.